Penggunaan Alat Musik Perkusi dalam Meningkatkan Kemampuan Motorik Kasar pada Anak Cerebral Palsy di SLB YPAC Makassar - Ariyandi, Yuzril; Hadis, Abdul; Meidina, Tatiana (-, 2025)
This research examines gross motor skills in cerebral students palsy at SLB YPAC Makassar. The problems studied in this research is low gross motor skills in cerebral palsy students. As for the problem formulation that the author raises is "What is the ability Gross motor skills in Cerebral Palsy children after using percussion musical instruments children with cerebral palsy at SLB YPAC Makassar?” this research is quantitative research and a type of descriptive research, namely for describe the results of increasing gross motor skills in children cerebral palsy after being given treatment using musical instruments percussion. The data collection technique used was an action test. The subjects in this research were class IV cerebral palsy students at SLB YPAC Makassar. The data analysis technique used is descriptive analysis technique. The results of the study showed that gross motor skills in children cerebral palsy using percussion instruments at SLB YPAC Makassar before being given treatment were in the underprivileged category. WhereasThe research results show that gross motor skills in students cerebral palsy using percussion instruments at SLB YPAC Makassar after being given treatment, they are in the capable category. This means there is increasing gross motor skills in cerebral palsy students in SLB YPAC Makassar using percussion instruments. Conclusions of this research shows that the use of percussion musical instruments can be effective improving gross motor skills in cerebral palsy students in SLB YPAC Makassar.